Strategi Komunikasi Dakwah Wilayatul Hisbah dalam Pencegahan Pelanggaran Qanun Aceh tentang Jinayat di Aceh Barat - nurjanah nurjanah (Jurnal Ilmu Dakwah, 2019)
Wilayatul Hisbah responded to the high level of violations of the Qanun Jinayat in Aceh. The process of minimizing violations is carried out through the propaganda communication strategy. This article aims to find the communication strategy of preaching Wilayatul Hisbah West Aceh in preventing violations of the Aceh Qanun Number 6 of 2014 concerning Jinayat. The method used is qualitative-descriptive. Data collection techniques carried out by observation, interviews and documentation. The results showed that the Wilayatul Hisbah missionary communication strategy was a communicator strategy, a message strategy, a media strategy, and an effect strategy.Wilayatul Hisbah merespon tingginya tingkat pelanggaran Qanun Jinayat di Aceh. Proses meminimalisir pelanggaran dilakukan melalui strategi komunikasi dakwah. Artikel ini bertujuan untuk menemukan strategi komunikasi dakwah Wilayatul Hisbah Aceh Barat dalam pencegahan pelanggaran Qanun Aceh Nomor 6 Tahun 2014 tentang Jinayat. Metode yang digunakan adalah kualitatif-deskriptif. Teknik pengumpulan data dilakukan dengan  observasi, wawancara dan dokumentasi. Hasil penelitian menunjukkan strategi komunikasi dakwah Wilayatul Hisbah adalah strategi komunikator, strategi pesan, strategi media, dan strategi efek.